Simulation of Oxygen Mass Transfer in an Internal Loop Airlift Reactor with Axial Dispersion Model - Atiya, Mohammed A.; Rahman, Ameel Mohammed; Abd Al-Jabbar, Aseel (Al-Khwarizmi Engineering Journal, 2011)
The effect of superficial gas velocity within the range 0.01-0.164 m/s on gas holdup (overall, riser and down comer), volumetric oxygen mass transfer coefficient, liquid circulation velocity was studied in an internal loop concentric tubes airlift reactor (working volume 45 liters). It was shown that as the usg increases the gas holdup and also the liquid circulation velocity increase. Also it was found that increasing superficial gas velocity lead to increase the interfacial area that increases the overall oxygen mass transfer coefficient. The hydrodynamic experimental results were modeled with the available equations in the literature. The predicted data gave an acceptable accuracy with the empirical data.The final empirical and predicted data were adopted in a mathematical model for oxygen mass transfer to predict the oxygen profile along the reactor. The predicted results have been validated with the experimental results. The simulated results based on the dispersion model for the riser and down comer and the perfect mixed model for the gas-liquid separator, agreed well with the experimental results over the studied range of operating conditions.